Path planning for visual servoing with search algorithm - Wang, Ting-Ting; Han, Xue; Zhou, Jun; Chen, Hua (Advances in mechanical engineering, 2018)
To solve the visual servoing tasks in complex environment, a path planning method based on improved rapidly exploring random trees algorithm is proposed. First, the improved rapidly exploring random trees planning method is adopted, which keeps the observed feature points in the field of view. The start node and the desired node are initialized as roots of multi-trees which grow harmoniously to plan path of the robot. Then, the planned path is used to project the three-dimensional target feature points into the image space and obtain the feature trajectory for the image-based visual servoing controller. Finally, the feature trajectory is tracked by the image-based visual servoing controller. The proposed visual servoing design method takes field of view constraints, camera retreat problem, and obstacle avoidance into consideration, which can significantly improve the ability of the robotic manipulator, especially in the narrow space. Simulation and experiment on 6-degree-of-freedom robot are conducted. The results present the effectiveness of the proposed algorithm.